Individual Characteristics, Competence, and Communication: Unleashing Employee Productivity: Karakteristik Individu, Kompetensi, dan Komunikasi: Meningkatkan Produktivitas Kerja Karyawan - Nadianita Amelinda; Slamet Harjatno (Academia Open, 2023)
This study investigates the relationship between individual characteristics, competence, and communication on employee performance, with work productivity as the mediating variable. The aim was to explore the effect of these factors on both work productivity and employee performance in the context of UKM Handoko Commodity Adventure. Non-probability sampling using the Saturated Sampling method was employed, and data was analyzed using path analysis with the SPSS application. The results revealed significant associations between individual characteristics, competence, and communication with both work productivity and employee performance. Furthermore, work productivity was found to mediate the relationship between these factors and employee performance. These findings shed light on the critical role of individual characteristics, competence, and communication in enhancing work productivity and employee performance, suggesting the importance of targeted interventions and strategies for optimizing organizational outcomes. Highlights: Individual characteristics, competence, and communication significantly influence employee performance and work productivity. Work productivity acts as a mediator between individual characteristics, competence, communication, and employee performance. Understanding and optimizing individual characteristics, competence, and communication can unleash employee performance and enhance work productivity. Keywords: Employee Performance, Individual Characteristics, Competence, Communication, Work Productivity.